Uji Organoleptik Kandungan Air dan Titik Beku Susu Sapi Perah yang diberi Ransum Lengkap Tersuplementasi Protein, Lemak, Mineral, dan Direct Fed Microbial - Bambang Kholiq Mutaqin; Didin Supriyat Tasripin; Lovita Adriani; Ujang Hidayat Tanuwiria (Jurnal Teknologi Hasil Peternakan, 2020)
The purpose of this study was to determine the simplest quality of milk with organoleptic tests (color, taste, flavour) and milk content of dairy cows before and after treatment. In vivo testing was carried out at PT. Citra Agro Buana Semesta (CABS) Malangbong. The study design used a completely randomized design (CRD) with 4 treatments and 4 replications. Treatment P1: Complete Ration, P2: P1 + DFM, P3: P1 + DFM + Protein by pass, P4: P1 + DFM + PFM. Analysis of organoleptic test results using the Friedman test and water content in dairy cows was tested by analysis of variance with Duncan's advanced test. Organoleptic research results and water content in milk of dairy cows showed a significant (p<0,05 The organoleptic test results for each treatment showed changes to the control treatment and the low water content obtained in the complete feed supplemented with DFM and PFM that was 86,74 ± 0,609%.